PENGEMBANGAN AKTIVITAS WISATA DI KAWASAN BUMI SAMAMI KOTA BANDUNG - Nike Cinthia Trigiani, - (2017)
Bumi Samami merupakan kawasan serbaguna yang berada di Kota Bandung. Terletak di Utara Kota Bandung tidak jauh dari perkotaan. Bumi Samami memiliki dua konsentrasi bisnis yaitu venue untuk acara dan guest house. Luas dan fasilitas yang dimiliki Bumi Samami menjadi salah satu potensi untuk pengembangan aktivitas wisata yang bisa dilakukan oleh pengunjung yang menginap di Bumi Samami. Penelitian ini menggunakan metode kualitatif. Teknik analisis data yang digunakan adalah memakai tahapan proses pengembangan menurut Yoeti (1996: 172) terdapat tiga syarat untuk memenuhi kriteria suatu daya tarik atau aktivitas wisata yaitu something to see, something to buy, dan something to do. Saran untuk pihak pengelola Bumi Samami agar mengembangkan keragaman aktivitas di Bumi Samami guna meningkatkan jumlah pengunjung. Bumi Samami is a multipurpose area in the city of Bandung. Located in the North of Bandung city, near from urban areas. Bumi Samami has two business concertation that is venue for the event and guest house. Spacious and facilities belonging to the Bumi Samami to be one of the potensial for development of tourist activity that can be order by visitors who stay at the Bumi Samami. This research purpose to develop tourist activities in the area of the Bumi Samami so the visitors came to Bumi Samami can do excursions. This study uses qualitative methods. Using data analysis techniques is the stages of the planning process according to Yoeti (1996: 172) there are three conditions to meet the criteria an atraction or tourist activity that is something to see, something to buy, and something to do. Advice to officials of the Bumi Samami in order to expand the diversity of the Bumi Samami activities in order to increase the number of visitors.